CURRENT STATUS OF TREATMENT ADHERENCE AMONG OUTPATIENTS WITH TYPE 2 DIABETES MELLITUS AT THE THANH HOA REGIONAL MEDICAL CENTER, TAY NINH PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the status of treatment adherence among outpatients with type 2 diabetes mellitus at Thanh Hoa regional Health Center, Tay Ninh province, in 2025, and to identify factors associated with overall treatment adherence.Subjects and methods: A descriptive cross-sectional study was conducted among 384 patients diagnosed with type 2 diabetes mellitus who were receiving outpatient treatment at Thanh Hoa regional Health Center from October to December 2025. Treatment adherence was assessed and described across four domains: dietary adherence, medication adherence, adherence to physical activity, and adherence to blood glucose monitoring and scheduled follow-up visits.Results: The overall rate of treatment adherence was 44.79%. Adherence to blood glucose monitoring and scheduled follow-up visits reached 100%, medication adherence was 93.49%, dietary adherence was 74.22%, and adherence to physical activity was 58.85%. Factors significantly associated with overall treatment adherence included age and the presence of complications: patients aged < 60 years demonstrated higher adherence than those aged ≥ 60 years, and patients with diabetes-related complications showed higher adherence compared with those without complications (p < 0.05).Conclusion: The overall treatment adherence rate among outpatients with type 2 diabetes mellitus receiving care at Thanh Hoa regional Health Center was low, at 44.79%. Targeted and comprehensive interventions are required to improve overall treatment adherence, thereby achieving better glycemic control, reducing the risk of complications, and enhancing patients’ quality of life.
Keywords: Treatment adherence, type 2 diabetes mellitus, outpatients.